Evaluation of anti-ulcer activity of hydromethanol crude extract and solvent fractions of Vicia faba (Fabaceae) seeds in mice - Demis Getachew; Alemante Tafese Beyna; Mohammedbrhan Abdelwuhab; Assefa Belay Asrie (PLoS ONE, 2025)
Peptic ulcer disease affects 10% of the global population, and current treatments have limitations. Vicia faba seeds are traditionally used in Ethiopia for gastric ulcers and gastritis, but scientific evidence is lacking. Seeds were extracted with 80% hydro-methanol to evaluate its antiulcer effect, and part of the extract was fractionated into n-hexane, ethyl acetate, and aqueous solvents. The antiulcer activity of the crude extract and solvent fractions was tested using pylorus ligation and ethanol-induced ulcer models. Repeated dose studies were also performed on both models. In a pylorus ligation-induced ulcer model, single-dose studies showed that 200 mg/kg significantly reduced ulcer number, score (P < 0.05), and index (P < 0.01), providing 39.83% protection. The 400 mg/kg, significantly reduced ulcer number, and score (P < 0.01), providing 55.80% protection. In a repeated-dose study, 100 mg/kg significantly reduced ulcer number and score (P < 0.05). The 200 mg/kg dose showed stronger effects (P < 0.01, for the above parameters, respectively). The highest dose (400 mg/kg) significantly reduced ulcer parameters (P < 0.001) and also lowered gastric juice volume (P < 0.01), acidity (P < 0.05), and raised pH (P < 0.01), providing 59.17% protection. In the ethanol-induced ulcer model, single-dose crude extract provided an ulcer index protection of 23.39%, 34.90%, and 54.04% at 100, 200, and 400 mg/kg, respectively. Repeated administration of the crude extract increased ulcer protection to 34.94%, 50.91%, and 65.72% at the same respective doses. All doses of the aqueous and the ethyl acetate fractions also showed antiulcer activity. This study confirmed that Vicia faba seeds crude extract and solvent fractions have significant antiulcer activity, providing scientific evidence supporting the traditional use of V. faba seeds as a remedy for gastric ulcers in Ethiopia.